2018
DOI: 10.4103/jrms.jrms_438_17
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral lichen planus and Epstein–Barr virus in Iranian patients

Abstract: Background:Oral lichen planus (OLP) is a common mucocutaneous disease with malignant transformation potential. Several etiologies such as humoral, autoimmunity, and viral infections might play a role, but still there is no definite etiology for this disease. The aim of this study was to investigate the presence of Epstein–Barr virus (EBV) genome in Iranian patients with OLP as compared to people with normal mucosa.Materials and Methods:The study was carried out on a case group including 38 tissue specimens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
(28 reference statements)
0
13
0
2
Order By: Relevance
“…The general characteristics of the included studies are summarized in Table 1. Ten case‐control studies 13‐16,20‐23,28,29 comprising 690 subjects (386 OLP cases and 304 healthy controls) were included in the present review; of these, 8 studies were eligible for the meta‐analysis 13‐16,20,21,28,29 . The studies were published between 1996 and 2018.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The general characteristics of the included studies are summarized in Table 1. Ten case‐control studies 13‐16,20‐23,28,29 comprising 690 subjects (386 OLP cases and 304 healthy controls) were included in the present review; of these, 8 studies were eligible for the meta‐analysis 13‐16,20,21,28,29 . The studies were published between 1996 and 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were conducted in Sweden, 16,23 two studies in Iran, 20,22 one study in Denmark, 13 one study in Turkey, 14 one study in Ireland, 29 one study in Hungary, 15 one study in Brazil, 15 and one study in India 28 . Seven studies 13,15,16,20‐23 reported gender of the participants, in which females comprised two thirds of subjects. The age of the included participants ranged between 18 and 81 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations